2000
DOI: 10.1002/(sici)1097-4660(200005)75:5<410::aid-jctb226>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of zinc(II) adsorption on Cladophora crispata in a two‐staged reactor

Abstract: In this study, the adsorption of zinc(II) ions on Cladophora crispata, a green alga, was studied with respect to initial pH, temperature, initial metal ion and biomass concentration in order to determine the optimum adsorption conditions. Optimum initial pH values for zinc(II) ions were found to be 5.0 at optimum temperature, 25°C. The initial adsorption rates increased with increasing initial zinc(II) ion concentration up to 100 mgdm À3. The Freundlich and Langmuir adsorption isotherms were developed at vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…in solution dropped rapidly within the time interval 5-15 min, with an apparent equilibrium being established after 30 min. Ahuja et al (1999) andÖ zer et al (2000) observed a similarly rapid physical adsorption within the initial 15 min of contact, and maintenance of that level over the time remaining. This fast disappearance of Zn ions in solution suggests that the metal removal by thermally inactivated cells occurs exclusively by adsorption onto the microalga cell surface, i.e.…”
Section: Metal Removal By Inactivated Cellsmentioning
confidence: 77%
“…in solution dropped rapidly within the time interval 5-15 min, with an apparent equilibrium being established after 30 min. Ahuja et al (1999) andÖ zer et al (2000) observed a similarly rapid physical adsorption within the initial 15 min of contact, and maintenance of that level over the time remaining. This fast disappearance of Zn ions in solution suggests that the metal removal by thermally inactivated cells occurs exclusively by adsorption onto the microalga cell surface, i.e.…”
Section: Metal Removal By Inactivated Cellsmentioning
confidence: 77%
“…Conversely, removal of metals by dead biomass entails only a passive process, with metal cations being predominantly adsorbed onto the functional groups on the cell surface. Surprisingly, dead biomass may, in some instances, provide a higher capacity for metal uptake than viable one 4, 66, 83. Furthermore, it entertains reversible phenomena that allow regeneration (and thus reuse) of the biomaterial in multiple sorption/desorption cycles as well as recovery of the metal removed from solution 11, 66.…”
Section: Microalga‐mediated Recovery Of Metalsmentioning
confidence: 99%
“…However, using them for metal removal in areas away from the sea coast may not be economically feasible. The potential of filamentous algae in removing metal ions from solution remains largely unexplored, except for a few reports (Aksu et al 1996;Ö zer et al 2000;Nuhoglu et al 2002;Mohapatra and Gupta 2005).…”
Section: Introductionmentioning
confidence: 99%